The Effect of Prenatal Yoga Exercise on The Back Pain of Pregnant Women in 3rd Trimester in The Kampung Jabi Health Centre Batam City - Hidayah, Nurul; Sari , Desi Pramita; Rosyidah, Haqqelni Nur (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: Back pain was a common disorder which occurred in pregnancy, pregnant women might have had a history of previous back pain. In order to overcome back pain could be done by yoga gymnastics which which was beneficial to form a strong posture, purifying the central nerves found in the spine. Objective: This research aimed to know the effect of Prenatal Yoga Exercise on the back pain of pregnant women in 3rd trimester In The Kampung Jabi Health Centre, Sub District Of Nongsa, Batam City. Method: This research type was preexperimental with the design of two group pretest posttest design. The populations of this research were all 3rd trimester pregnant In The Kampung Jabi Health Centre, Sub-District of Nongsa, Batam  City which amounted to 51 pregnant women. The samples were 45 pregnant women which were taken by purposive sampling. The independent variable was yoga gymnastics and the dependent variable was back pain of pregnant women in 3rd trimester. The research instrument used a questionnaire. Data processing used editing, coding, scoring, tabulating with data analysis of spearman Rank. Result: The research result showed thats before being conducted Prenatal Yoga Exercise almost a half of pregnant women experienced back pain with scale 2 (a little more pain) as many as 44,4% with 20 respondent while after being conducted Prenatal Yoga Exercise almost a half of pregnant women experienced back pain with scale 1 (little pain) as many as 48,9% with 22 respondent. The statistical test of Spearman rank showed thats value = 0,001 <  (0,05) so H1 was accepted. Conclusion: There is an effect of Prenatal Yoga Exercise on the back pain of pregnant women in 3rd trimester. It was expected for pregnant women to follow if there would be yoga gymnastics, which would be useful to overcome back pain, if there are not pregnant women can do self at home.